Testing and commisioning of GIS switchgear for high voltage substation / Mohd Zulkifli Mat Ghani - Mat Ghani, Mohd Zulkifli (2003)
This project presents a testing and commissioning of high voltage substation. The project focus on Gas Insulated Switchgear (GIS) is come out and the result of testing obtained are compared with Air Insulated Switchgear (AIS). The study and testing is carried out at Bukit Raja substation for GIS and Tanah Merah for AIS. The testing focus at primary side includes busbar, switchgear and Transformer. The testing includes busbar, switchgear and transformer. The testing to make sure all equipment can be operate and safe for used. In this project, we can see protection of GIS substation comparison with AIS substation.